Limited research investigating the value of MRI in predicting future cognitive morbidity in survivors of paediatric brain tumours: A systematic-review and call to action for clinical neuroimaging researchers - Daniel J. Griffiths-King; Christopher Delivett; Andrew Peet; Jane Waite; Jan Novak (PLoS ONE, 2025)
Survivors of pediatric brain tumours are at a high risk of cognitive morbidity. Reliable individual-level predictions regarding the likelihood, degree, and affected domains of cognitive impairment would be clinically beneficial. While established risk factors exist, quantitative MRI analysis may enhance predictive value, above and beyond current clinical risk models. This systematic review addresses the question: “Do MRI markers predict future cognitive functioning in pediatric brain tumour survivors?” We conducted a comprehensive search for studies published up to March 2024 that assessed MRI variables as predictors of later neuropsychological outcomes in pediatric brain tumour patients. Only studies that acquired MRI scans at an earlier timepoint to predict subsequent cognitive test performance were included. Surprisingly, few studies met these criteria, with identified research focusing primarily on MRI measures of cerebellar and white matter damage as features in predicting cognitive outcomes. Ultimately, this review reveals a limited literature, characterized by small sample sizes and poor-quality studies, placing findings at high risk of bias. Consequently, the quality and conclusions drawn from the existing research are constrained, especially in the context of prediction studies. Given the significant implications for this clinical population, this review highlights the urgent need for further investigation and a ‘call to action’ for medical imaging researchers in pediatric neuro-oncology.